Sensorial, chemical and microbial quality of spongy rosogolla - Hossain, MS; Khandakar, MMH; Islam, MN; Islam , MA (Bangladesh Journal of Animal Science, 2022)
The goal of this investigation was to compare the physical, chemical and microbial qualities of laboratory made and market spongy rosogolla. Two types of spongy rosogolla were made in laboratory from the cow and buffalo milk chhana to reveal the quality in regards of the species and three types of market spongy rosogolla were collected from three different shops. With regard to the physical attributes, laboratory made spongy rosogolla were found better than the market spongy rosogolla and cow milk spongy rosogolla was the best. In chemical aspects, laboratory made spongy rosogolla had greater pH, fat, protein, and ash content, whereas, market spongy rosogolla showed higher acidity and carbohydrate content. The moisture content of cow milk spongy rosogolla was highest. The mineral contents (Ca, P, and Mg) were also differed significantly (p<0.01) among the samples except for Na content. Highest Ca, P and Mg contents were found in market spongy rosogolla. The total viable count (TVC) was significantly (p<0.01) lower in laboratory made spongy rosogolla. However, the Escherichia coli count was found similar (p>0.05) in both cow and buffalo milk spongy rosogolla but lower (p>0.05) than other market spongy rosogolla samples. Considering all the findings, it may be concluded that the quality of market spongy rosogolla needs improvement and responsible authorities might take necessary initiatives for monitoring. Bangladesh Journal of Animal Science, 51 (2): 81-84.